2009
DOI: 10.1258/ijsa.2008.008325
|View full text |Cite
|
Sign up to set email alerts
|

How do UK medical graduates rate their knowledge and skills in sexual health and HIV medicine? A national survey

Abstract: The objectives of this study are to determine self-assessed knowledge and skills in sexual health and HIV medicine in preregistration house officers and to explore undergraduate experiences of teaching and assessment in these subjects prior to the launch of National Core Learning Outcomes in Sexual and Reproductive Health and HIV. The study was designed as a postal questionnaire survey. The participants were all UK medical graduates of August 2004. The response rate 1737/4746 (36%). The main outcome measures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Studies of medical students, residents, and practicing physicians have documented that HIV risk behavior continues to go unidentified, and that counseling on HIV prevention is ineffective (Curtis et al 1994;Cook et al 1998;Liddicoat et al 2004). A survey of British medical graduates found that less than 45% felt that they could conduct an appropriate HIV pre-test discussion, and less than 60% felt that they could recognize clinical indicators suggestive of HIV (Estcourt et al 2009). This competency is especially relevant given that many individuals are unaware of their HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of medical students, residents, and practicing physicians have documented that HIV risk behavior continues to go unidentified, and that counseling on HIV prevention is ineffective (Curtis et al 1994;Cook et al 1998;Liddicoat et al 2004). A survey of British medical graduates found that less than 45% felt that they could conduct an appropriate HIV pre-test discussion, and less than 60% felt that they could recognize clinical indicators suggestive of HIV (Estcourt et al 2009). This competency is especially relevant given that many individuals are unaware of their HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, possibly more concerning is that in a recent survey of UK junior doctors, who graduated in 2004, less than half of them felt they could conduct an appropriate HIV pre-test discussion and only 59% felt confident that they could recognize clinical indicators suggestive of HIV. 6…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Yet, evidence indicates that education in sexual health appears to increase physician willingness to manage such concerns. [12][13][14] Similarly, educational interventions can improve provision of care for HIV patients, both in terms of healthcare worker knowledge and attitudes. 15 Thus, one necessity for the interruption of the current STI and HIV pandemics is education of physicians in their management.…”
Section: Introductionmentioning
confidence: 99%